The Result Of Study Biology Observed From Preview, Question, Read, Reflect, Recite, Review (PQ4R) Learning Method and learning Interest Of Student’s on X Grade Of Sma Negeri 1 Kebakkramat In Academic Year 2011/2012 - Arum Yulistiati; Alvi Rosyidi; Joko Ariyanto (BIO-PEDAGOGI, 2012)
The purposes of this research were to know: 1) the influence of Preview, Question, Read, Reflect, Recite, Review (PQ4R) learning metod to the result of study biology; 2) the influence of student’s learning interest to the result of study biology; 3) the interaction between learning metod and learning interest to the result of study biology: and 4) the influence of better learning metod to the result of study biology. This research was quasi experiment research using Randomized Control Only design. Learning metod and learning interest were independent variables and student’s achievement of study biology was the dependent variable. The population of this research was all of  X grade of natural science students of SMA Negeri 1 Kebakkramat. The samples of this research were the students of class X-5 as the control group and students of class X-4 as the experimental group.  The sample of this research was established by cluster random sampling. The data about the result of study biology collected by use test and observation. Learning interest meansured by using questionnaires. The analisis of this research was anava two away in different cell and the advance test used Bunfferoni test. The conclusion of this research were: 1) Preview, Question, Read, Reflect, Recite, Review (PQ4R) learning metod had significant influence to the result of study biology in cognitive domain on X grade of SMA Negeri 1 Kebakkramat; 2) Learning interest had significant influence to the result of study biology on X grade of SMA Negeri 1 Kebakkramat; 3) There wasn’t interaction between learning metod and learning interest to the result of study biology on X grade of SMA Negeri 1 Kebakkramat: and 4) Preview, Question, Read, Reflect, Recite, Review (PQ4R) learning metod was better than conventional to the result of study biology in cognitive domain on X grade of SMA Negeri 1 Kebakkramat.